STRATEGI KOMUNIKASI DALAM PROGRAM TELECENTER DI PROPINSI JAWA TIMUR - Niken Lestari (Jurnal Sosiologi Reflektif, 2016)
This paper discusses the communication strategy developed by telecentres and challenges faced by the manager. The purpose of this paper is to analyze the effective communication strategy in the extension process conducted through telecenters. The primary data obtained through field visits, observation, and interviews with managers of telecenters. Meanwhile secondary data obtained from writings made by telecenter managers on the internet and the data from the Communications and Information Technology Ministry. Telecenter in Indonesia is designed as a community development center to hold activities such as training, improvement of skills and knowledge as well as the implementation of economic activity. Based on data from Communications and Information Technology Ministry, East Java is the province that has the most telecenters because it was developed with cost sharing between provinces and districts budget. The analysis showed that the telecentres implement 10 stages of Wilson’s strategy with some adjustments. The role of the Office of Communications and Information Technology is very crucial in the planning and management of communication so that there should be capacity building for the officers. The challenges are about the institutional strengthening (organizational structure obscurity) and the unavailability of sources of information in accordance with the level and/or pattern of knowledge in rural communities. Infomobilisator role as an educator is very important given the complexity of the issue and the large amount of information in the internet. Telecenter was considered successful in creating a interconnectedness between individuals and between groups (communities). However, the impact related to increased prosperity for farmers have not been prominent. For the old generation of farmers, information about the price of commodities, seeds, and means of support have not become a real need and a felt need. Therefore, it is the role of infomobili sator to achieve intermediate objectives in order to reach the ultimate goal of poverty reduction.Tulisan ini membahas tentang strategi komunikasi yang dikem bang kan oleh telecenter dan tantangan yang dihadapi oleh pengelola. Tujuan tulisan ini yaitu menganalisis strategi komunikasi yang efektif dalam proses penyuluhan yang dilaku kan melalui telecenter. Data primer diperoleh melalui kunjungan lapangan, pengamatan, dan wawancara dengan pengelola telecenter. Sementara data sekunder diperoleh dari tulisan yang dibuat pengelola telecenter di internet dan data dari Kominfo. Telecenter di Indonesia dirancang sebagai tempat kegiatan pemberdayaan masya  rakat berupa pelatihan, peningkatan ketrampilan, dan pengetahuan serta pelaksanaan kegiatan ekonomi. Berdasarkan data Kominfo, Jawa Timur merupakan provinsi yang memiliki paling banyak telecenter karena dikembangkan dengan pola pembiayaan bersama antara provinsi dengan kabupaten. Hasil analisis menunjukkan bahwa telecenter menerapkan 10 tahap strategi Wilson dengan bebe rapa penyesuaian. Peran Dinas Kominfo provinsi sangat besar dalam proses perencanaan dan manajemen komunikasi sehingga perlu ada peningkatan kapasitas SDM Dinas Kominfo terkait kedua hal tersebut. Tantangan yang dihadapi pengelola yaitu seputar kelembagaan (ketidakjelasan struktur organisasi) dan tidak tersedianya sumber informasi yang sesuai dengan tingkat dan/atau pola pengetahuan masyarakat desa. Peran infomobilisator sebagai penyuluh sangat penting mengingat kompleksitas isu dan jumlah informasi yang sangat besar di internet. Telecenter dianggap berhasil menciptakan “keterhubungan” (interconnectedness) antar perorangan dan antar kelompok masyarakat (komunitas). Namun dampaknya bagi peningkatan kesejahteraan bagi petani belum menonjol. Bagi petani generasi lama, informasi seputar harga komoditi, bibit, sarana pendukung belum menjadi real need dan felt need. Oleh karena itu, peran infomobilisator sangat penting untuk membantu mencapai tujuan antara sebagai jembatan ke tujuan akhir yaitu pengentasan kemiskinan.